Controlled Bioactive Molecules Delivery Strategies for Tendon and Ligament Tissue Engineering using Polymeric Nanofibers - Kok Hiong Teh, Thomas; Cho Hong Goh, James; Lok Toh, Siew (Current Pharmaceutical Design, 2015)
The interest in polymeric nanofibers has escalated over the past decade given its promise as tissue engineering scaffolds that can mimic the nanoscale structure of the native extracellular matrix. With functionalization of the polymeric nanofibers using bioactive molecules, localized signaling moieties can be established for the attached cells, to stimulate desired biological effects and direct cellular or tissue response. The inherently high surface area per unit mass of polymeric nanofibers can enhance cell adhesion, bioactive molecules loading and release efficiencies, and mass transfer properties. In this review article, the application of polymeric nanofibers for controlled bioactive molecules delivery will be discussed, with a focus on tendon and ligament tissue engineering. Various polymeric materials of different mechanical and degradation properties will be presented along with the nanofiber fabrication techniques explored. The bioactive molecules of interest for tendon and ligament tissue engineering, including growth factors and small molecules, will also be reviewed and compared in terms of their nanofiber incorporation strategies and release profiles. This article will also highlight and compare various innovative strategies to control the release of bioactive molecules spatiotemporally and explore an emerging tissue engineering strategy involving controlled multiple bioactive molecules sequential release. Finally, the review article concludes with challenges and future trends in the innovation and development of bioactive molecules delivery using polymeric nanofibers for tendon and ligament tissue engineering.
Keywords: growth factors